KOMPARASI EFISIENSI MATERIAL BAJA KARBON St 37, BAJA KARBON St 41 DAN BAJA KARBON St 60 TERHADAP LAJU KOROSI DI MEDIA AIR MUARA SUNGAI (PAYAU) DENGAN METODE ELEKTROKIMIA - Yusuf Nur Afandi; Sumarji Sumarji (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2013)
Mouth of the river is the meeting place of river water and sea water . water estuaries (brackish water) has asodium chloride content of between 1% -2.5 whether it's from natural sources around the surrounding river water or a mixture of sea water . many construction or structure that is attached to the mouth of the river environment made of metal materials, especially carbon steel. the use of steel in building structures in estuaries susceptible to corrosion due to environmental water containing chemical elements that are corrosive. Factors affecting corrosion such as temperature, acidity (pH), salinity (NaCl), the levels of chloride (Cl), the levels of sulfate (SO) as well as dissolved oxygen, causing easily corroded carbon steel. This study aims to determine the Comparative Efficiency of Steel St 37, St 41 Steel and Steel st 60 on the rate of corrosion in aqueous media estuaries with tool Potensiostat methods. This research is an experimental laboratory to design the post-test group design. From the results obtained data show the results of corrosion rate measurements made in this study that the greatest rate of corrosion occurring on the steel material St 37 is 29.527 mpy, St 41 steel was 27.548 mpy, and steel St 60 is 24,493 mpy. The results showed that the corrosion rate of steel st 37 has a very large corrosion rate in comparison steel and carbon steel st 41 high st 60. From the observation in micro on the trid specimen three is corrosion that resembles a uniform or evenly corrosion. A form of corrosion that results in a uniform attack on the entire surface of the metal. Keywords: Estuaries, The Rate of Corrosion